Molecular phylogenetic analysis of a known and a new hydrothermal vent octopod: their relationships with the genus Benthoctopus (Cephalopoda: Octopodidae) - Strugnell, Jan; Voight, Janet R.; Collins, Patrick C.; Allcock, A. Louise (Zootaxa, 2009)
The resolution of evolutionary relationships among deep-sea incirrate octopuses has been hindered by the paucity of individuals available for morphological studies and by the lack of tissue samples preserved using fixatives compatible with simple DNA extraction techniques. Evolutionary relationships from 11 species of deep-sea incirrate octopuses were investigated using 2392 base pairs (bp) of DNA from four mitochondrial genes (12S rDNA, 16S rDNA, cytochrome c oxidase subunit III, and cytochrome b) and the nuclear gene, rhodopsin. Morphological examination of these species was also undertaken. Molecular analyses distinguish a species of octopus from hydrothermal vents at Manus Basin from the vent octopodid Vulcanoctopus hydrothermalis known from vents on the East Pacific Rise. Both are herein considered members of the clade currently assigned the name Benthoctopus, although taxonomic implications preclude formally naming Vulcanoctopus as a junior synonym. Morphological investigations led to the conclusion that Benthoctopus macrophallus is a junior synonym of Benthoctopus yaquinae. An amended diagnosis of Benthoctopus is provided with additional information on male reproductive characteristics.